OC-015 The Influence of Gender and Haemoglobin on TPMT Activity. (4th June 2013) - Blaker, P A; Kariyawasam, V C; Patel, K V; Goel, R M; Ward, M G; Irving, P M; Marinaki, A M; Sanderson, J D
Abstract : Introduction: Pre-treatment measurement of red blood cell (RBC) thiopurine- S- methyltransferase (TPMT) activity is recommended to guide initial dosing of azathioprine (AZA) and mercaptopurine (MP). TPMT exhibits a trimodal distribution, with low and intermediate activities predicting myelotoxicity at standard drug doses. There is a high concordance between TPMT genotype and normal or low enzyme activity (93–100%); however the relationship is poor in the intermediate range (53–100%) [1] . Furthermore, there are few explanations for the wide variation in inter-individual TPMT activities in the wild-type range. Bioavailability of the cofactor S -adenosylmethionine (SAM) and RBC age may play a role. The aim of this study was to determine if gender or anaemia influences RBC TPMT activity. Methods: We analysed a retrospective cohort of 6, 496 RBC TPMT samples (n = 3804 females, n = 2692 males) measured in the PRL since 2004 and correlated enzyme activity with gender and haemoglobin concentrations. Results: A greater portion of females exhibited intermediate TPMT activity (13.46%) as compared to males (11.07%). The mean TPMT activity was also significantly lower in females (32.94 pmol/mg Hb/h) versus males (34.13 pmol/mg Hb/h; p = < 0.0001, 95% CI 0.7950–1.589). When separated by low, intermediate or normal TPMT activity, this relationship only remained in patients with normal TPMT activity. TPMT activity was significantly higher in female patients with an Hb < 10g/dl (n = 250, mean TPMT 38.06 pmol/mg Hb/h) versus females with an Hb > 12g/dl (n = 2192, mean TPMT 32.46 pmol/mg Hb/h; p = < 0.0001). Similarly TPMT activity was significantly higher in male patients with an Hb < 10g/dl (n = 123, mean TPMT 38.14) versus males with an Hb > 12g/dl (n = 1901, mean TPMT 33.76; p = < 0.0001). Conclusion: TPMT activity in the wild-type range is lower in females than males, suggesting a post-translational influence on TPMT activity related to gender. Lower levels of SAM have been reported in females, which may explain this observation[2]. Re-appraisal of the concordance between TPMT genotype and phenotype, adjusting for gender is therefore indicated. The finding of higher TPMT activity with anaemia may be due to a younger red cell population in this group. The difference in TPMT activities between patients with or without anaemia is clinically relevant, particularly where the TPMT activity is around the cut-off between intermediate (10–25 pmol/mg Hb/h) and normal (≥26 pmol/mg Hb/h) ranges. TPMT genotyping should be considered in such patients. Disclosure of Interest: None Declared References: Karas-Kuzelicki, et al. Pharmacogenomics 2009. 10:1309–22. Poirier, et al. Cancer epidemiology, biomarkers & prevention 2001. 10:649–655.